Prevalence of Sarcopenia in Older South African Patients Following Surgery for Fragility Fractures of the Hip - Cornelius V. Laubscher MBChB; Marilize C. Burger BSc, BMedSc(Hons), MMedSc, PhD; Maria M. Conradie BSc, MSc; Magda Conradie MBChB, PhD; Jacobus D. Jordaan MBChB, H Dip Orth(SA), FC Orth(SA) (Geriatric Orthopaedic Surgery & Rehabilitation, 2020)
Introduction: Geriatric patients with a fragility fracture of the hip (FFH) are especially prone to sarcopenia with poor functional outcomes and quality of life. We assessed the prevalence of sarcopenia in older South African patients with FFH. Risk factors for sarcopenia were also investigated. Materials and Methods: From August 1 to November 30, 2018, all older patients with FFH were invited to participate. Sarcopenia was diagnosed based on the revised criteria of the European Working Group on Sarcopenia in Older People (EWGSOP2). Handgrip strength (HGS) and muscle strength were assessed. Muscle quantity was determined by dual-energy X-ray absorptiometry. Demographic information was collected, and 25-hydroxyvitamin D (25[OH]D) status was determined. Results: Of the 100 hip fracture cases, 65 were enrolled, and 52% (34/65) were sarcopenic (women: 62%; men: 38%). HGS accurately identified sarcopenia (sensitivity and specificity: 100%). Patients >80 years of age had a prevalence of sarcopenia twice (18/21 [83%]) that of younger patients (18/44 [36%]). Women with sarcopenia were smaller than those without (weight: p < 0.001; height: p < 0.001; body mass index: p = 0.018). Low 25(OH)D was almost universally present, with median 25(OH)D levels significantly lower in the patients with sarcopenia (27 nmol/L [interquartile range IQR: 20–39] vs. 40 nmol/L [IQR: 29–53]). Several risk factors, including advanced age; female sex; a smaller body size, especially among women; limited physical activity; and low 25(OH)D levels, were identified. Discussion: The accuracy of HGS testing in this cohort underscores EWGSOP2’s recommendation that muscle strength is key to sarcopenia. Further study and follow-up are required to determine the clinical relevance of sarcopenia among FFH patients. Conclusion: The prevalence of sarcopenia in our FFH population is high. Sarcopenia is associated with poor patient outcomes following surgical intervention. Orthopaedic surgeons should therefore be cognizant of the presentation and associated risk of sarcopenia as our patient populations age.